Dynamometric analysis of resisted sled on sprint run - Nogueira, M.; Viriato, N.; Vaz, M.; Carvalho, J.; Conceicao, F. (ISBS - Conference Proceedings Archive (Konstanz), 2011)
The main purpose of this work was to perform a dynamometric analysis of the step in resisted sprint with sled towing, using different connection points (vest and belt) as well as distinct velocities (90% and 92,5% of the maximum speed). A sample of 8 male sprinters participants was constituted. Each individual performed 2 trials of 30m for each test. The data of GRF were collected through a force plate (Bertec 4060-15) placed at 20m from the starting line. Results pointed out that the vest seems to be advantageous for the propulsive phase of the support whilst the belt for the breaking phase of the support.